Investigating the incidence of fluorinating enzymes in dichapetalum cymosum and actinopolyspora mzabensis - Sooklal, Selisha Ann (My University, 2019)
Despite fluorine being the most abundant halogen in the earth’s crust, fluorinated metabolites are extremely rare in nature. The first fluorinated metabolite, fluoroacetate, was isolated from the plant Dichapetalum cymosum. Given the scarcity of fluorometabolites, the biosynthetic origin of fluoroacetate in D. cymosum was of great interest. However, the fluorination mechanism in plants was never elucidated and attention shifted to the bacterium Streptomyces cattleya, which was also found to produce fluoroacetate as well as 4-fluorothreonine. The first fluorinating enzyme, or fluorinase, was isolated from S. cattleya. Fluorinases have the unique ability to catalyse a C-F bond, hence, have vast potential as biocatalysts in the production of fluorinated products. But fluorinases are extremely rare enzymes and only five representatives have been isolated thus far. Therefore, efforts to expand enzymatic resources for biofluorination are highly desired. This study aimed to investigate D. cymosum on an omics level to gain insights into the potential fluorinating mechanism. D. cymosum presumably produces fluoroacetate as a defence mechanism, hence, mechanical wounding studies were performed and cDNA libraries of the unwounded (control) and wounded (30 and 60 minutes post wounding) plant were sequenced. The transcriptome assembly generated 77,845 transcripts, of which, 69% were annotated using various databases. This represents the first comprehensive transcriptome for D. cymosum. While the differential expression analysis revealed key wound-responsive transcripts related to signalling cascades, phytohormone regulation, transcription factors and some secondary metabolite defences; a transcript with homology to any known fluorinase was not detected. A functional screening based approach coupled with proteomic sequencing was then employed. A total of 2,430 proteins were detected. However, assays using the natural substrate of bacterial fluorinases did not yield any activity in D. cymosum. The lack of a transcript with homology to bacterial fluorinases and failure to detect activity using bacterial fluorinase substrates strongly suggests the presence of a different fluorinating enzyme in the plant kingdom. Efforts to expand fluorinase resources were extended to bacteria. We report on the identification of a novel fluorinase from Actinopolyspora mzabensis. A hypothetical protein sequence, herein denoted as Amfluorinase, was identified in the genome of A. mzabensis. Sequence alignments and homology models of this sequence revealed features characteristic of fluorinases, suggesting a promising new target. Thus, fluorination activity was validated experimentally. The gene was cloned into E. coli BL21 (DE3) cells. Overexpression of the Am-fluorinase resulted in the formation of insoluble inclusion bodies. A method for the recovery of the active enzyme from inclusion bodies is presented. Following purification, > 80 mg of the Am-fluorinase was obtained. Characterisation of the biochemical reaction confirmed fluorination activity. The optimal pH for activity was found at pH 7.2 while the optimal temperature for activity was found at 65 °C. At these conditions the enzyme exhibited a specific activity of 0.44 U/ mg. The presence of Mg2+ ions was also shown to increase relative activity by 10%. However, most intriguingly, the Am-fluorinase displayed exceptional stability at 25 °C indicating thermostability. The identification of a novel fluorinase in this study contributes to the biological tools available for fluorination. In addition, this is the first report on the successful refolding of a fluorinase enzyme and the method employed here can potentially be applied to other fluorinases to obtain high yields of the enzyme.
A thesis submitted in fulfilment of the requirements for the degree Doctor of Philosophy in Molecular and Cell Biology to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2019
Keywords: Dichapetalum; Organofluorine compounds; Fluorine--Toxicology